Characterization of medication advertisements in a popular US parenting magazine - Jennifer Mongiovi; Valerie Cadorett; Corey Basch (Tabriz University of Medical Sciences, 2017)
Background: Medication advertisements in magazines typically provide minimal educational benefit. This is of particular concern when targeted to caregivers responsible for making major medical decisions for their children. Methods: A cross-section of 72 issues from Parents magazine were collected and categorized by health condition and availability of the medication by prescription or over-the-counter (OTC).The type of medicine, dose, warning label, indication for child or adult, presence of a cartoon character, and the marketing theme used were documented. Chi-square analysis was used to determine significant differences in content. Results: Fewer than 30% (95% CI: 25.4%, 34.5%) of advertisements contained dosage information and approximately 50% (95% CI: 50.3%, 60.2%) contained side effect warnings. The greatest number of advertisements was for cold, cough and flu medications (14.7%; 95%CI: 11.6%, 18.6%).Conclusion: Medicine advertisements often do not include important information that could help consumers make informed decisions and avoid negative implications. Further research is needed to determine the attitudes of consumers to better understand and support consumers 'needs.